Food Security in Venezuela: Production and consumption in 2023 - Segovia López, Emma (Journal of the University of Zulia, 2022)
Data on food production and consumption in Venezuela are analyzed, as well as some projections for 2023, within the framework of National Food Security. For this purpose, the measurements and estimates of specialized organizations (national and international) and of the different associations of producers were consulted, through which the non-existence of official numbers has been supplied. Food Security and feeding in Venezuela have suffered a deterioration in each of its components; from availability, represented by national production; and access, reflected in the consumption and behaviour of the Venezuelan consumer. The projections for 2023 are favorable to advance in the progressive recovery of the national agricultural production, and in this way to supply the national market in more than 50% for most of the items of strategic importance. For this, it is necessary to implement changes in the structures of the agricultural policy of the Venezuelan State.